Adjuvant Radiotherapy After Minimally Invasive Surgery in Patients With Stage IA1-IIA1 Cervical Cancer - Gan, Yi-xiu; Du, Qing-hua; Li, Jian; Wei, Ye-ping; Jiang, Xu-wei; Xu, Xue-mei; Yue, Hai-ying; Li, Xiang-de; Zhu, Hui-jun; Ou, Xue; Zhong, Qiu-lu; Luo, Dan-jing; et al. (Frontiers in Oncology, 2021)
To estimate whether adjuvant radiotherapy is necessary for patients with stage IA1-IIA1 cervical cancer after laparoscopic hysterectomy, 221 patients were retrospectively analyzed. Sixty-two of them were treated with laparoscopic hysterectomy and adjuvant radiotherapy (group A), 115 underwent open surgery (group B) and 44 received laparoscopic hysterectomy alone (group C). Results showed that the 3-year local recurrence-free survival (LRFS) rates of group A, B and C were 98.4%, 97.4% and 86.4%, respectively. The LRFS rates of group A and B surpassed C (A vs. B, p=0.634; A vs. C, p=0.011; B vs. C, p=0.006). The inter-group differences of 3-year overall survival (OS) and distant metastasis free survival (DMFS) were not statistically significant. In subgroup analysis of stage IB disease, the 3-year LRFS rates of group A, B and C were 100%, 98.8% and 83.1%, the 3-year OS rates of group A, B and C were 100%, 98.9% and 91.5%, respectively. The 3-year LRFS and OS rates of group A and B were significantly superior to group C (p<0.05). Our findings suggest that adjuvant radiotherapy can reduce the risk of recurrence for women with early-stage cervical cancer after laparoscopic hysterectomy and bring survival benefits for patients with stage IB disease.